A difficult equilibrium: torture narratives and the ethics of reciprocity in apartheid South Africa and its aftermath - Pett, Sarah (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2009)
This thesis takes the form of an enquiry into the development of the "•generic contours (Bakhtin 4) for the narration of torture in South Africa during apartheid and its aftermath. The enquiry focusses on the ethical determinations that underlie the conventions of this genre. My theoretical framework uses Adam Zachary Newton's conceptualization of narrative ethics to supplement Paul Ricoeur's writings on narrative identity and the ethical intention, thus facilitating the transfer of Ricoeur's abstract philosophy to the realm of literary criticism. Part I presents torture as a disruption of narrative identity and a defamiliarization of the intersubjective encounter. The existence of torture narratives thus attests to the critical role of narration in the reconstruction of the tortured person's identity and the re-establishment of benign frameworks of intersubjective communication. Literature's potential to act as a laboratory for the testing of the limitations of narrative identity and the resilience of ethical mores suggests that the fictional representation of torture also has an important role to play in this attempt at rehabilitation. Part II takes the form of a comparative analysis of non-fictional and fictional accounts of torture originating from apartheid South Africa. This shows that the ethical determinations underlying the narration of torture in South Africa range from intersubjective estrangement to a "•solicitude of reciprocity (Bourgeois 109). However, because the majority of these texts used the presentation of human rights abuses to galvanize international opposition to apartheid, the scope for experimentation was limited by the political exigencies of the time. Part III examines the stylistic and generic shifts in the narration of torture that accompanied South Africa's transition to democracy. It suggests that the discursive dominance of the Truth and Reconciliation Commission replaced the fruitful"”in literary terms"”dialogue between authoritarianism and resistance that characterized the apartheid era with a monologic grand narrative of emotional catharsis, reconciliation and nation building. It also suggests that the "•truth-and-reconciliation genre of writing (Quayson 754) that shaped the literary milieu of the post-TRC period be seen in terms of a resurgence of the apartheid"“era paradigms for the narration of human rights abuses that were repressed during the initial phase of democratic transition. By framing the TRC as a catalyst for individual journeys of self-discovery, these novels raise important questions about what it means to be a part of the "•new South Africa. In contrast to the majority of apartheid era literature, the novels of the post-TRC period privilege the literary prerogative over the political, and thus bring to fruition the experimental potential of the previous paradigm. In doing so, they not only go beyond solicitude to achieve an "•authentic reciprocity in exchange (Ricoeur, Oneself 191), but also initiate a process of long-awaited literary expansion, in which authors look beyond the limits of apartheid and begin to critically engage with the region's pre-apartheid history and its post-apartheid present.
Keywords: Apartheid -- South Africa -- History; Torture -- South Africa; Post-apartheid era -- South Africa; Apartheid in literature; Torture in literature